Genetic Diversity and Microevolution of Burkholderia pseudomallei in the Environment - Chantratita, Narisara; Wuthiekanun, Vanaporn; Limmathurotsakul, Direk; Vesaratchavest, Mongkol; Thanwisai, Aunchalee; Amornchai, Premjit; Tumapa, Sarinna; Feil, Edward J.; Day, Nicholas P.; Peacock, Sharon J. (PLOS Neglected Tropical Diseases, 2008)
BackgroundThe soil dwelling Gram-negative pathogen Burkholderia pseudomallei is the cause of melioidosis. The diversity and population structure of this organism in the environment is poorly defined.Methods and FindingsWe undertook a study of B. pseudomallei in soil sampled from 100 equally spaced points within 237.5 m2 of disused land in northeast Thailand. B. pseudomallei was present on direct culture of 77/100 sampling points. Genotyping of 200 primary plate colonies from three independent sampling points was performed using a combination of pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Twelve PFGE types and nine sequence types (STs) were identified, the majority of which were present at only a single sampling point. Two sampling points contained four STs and the third point contained three STs. Although the distance between the three sampling points was low (7.6, 7.9, and 13.3 meters, respectively), only two STs were present in more than one sampling point. Each of the three samples was characterized by the localized expansion of a single B. pseudomallei clone (corresponding to STs 185, 163, and 93). Comparison of PFGE and MLST results demonstrated that two STs contained strains with variable PFGE banding pattern types, indicating geographic structuring even within a single MLST-defined clone.ConclusionsWe discuss the implications of this extreme structuring of genotype and genotypic frequency in terms of micro-evolutionary dynamics and ecology, and how our results may inform future sampling strategies.